If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 56 = -4x Reorder the terms: 56 + 4x = -4x Solving 56 + 4x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 56 + 4x + 4x = -4x + 4x Combine like terms: 4x + 4x = 8x 56 + 8x = -4x + 4x Combine like terms: -4x + 4x = 0 56 + 8x = 0 Add '-56' to each side of the equation. 56 + -56 + 8x = 0 + -56 Combine like terms: 56 + -56 = 0 0 + 8x = 0 + -56 8x = 0 + -56 Combine like terms: 0 + -56 = -56 8x = -56 Divide each side by '8'. x = -7 Simplifying x = -7
| x^3-6x^2-7x=0 | | 1.5x^4-5x^3-16x^2=0 | | x=20000*5/(20000+4700) | | 3=8x-5(3x+5) | | x=100000*5/(100000+4700) | | 8(2-3t)+7t-13=t+24 | | x=4700*5/(100000+4700) | | 12x-7(x+2)=10(x-1)-(5x+4) | | 7x=7(7)+85-6(8) | | 6q+8=7q+8 | | 2x+4y=36 | | -2x-2x=26-2 | | 6x=95 | | 4(5x+2)-3(x-2)=10x+(7x+9) | | x^2+5=8X-10 | | (13-z)z=0 | | x^2-2X-8=7 | | -2(5z-4)+6z=-4 | | 8+4(5x-2)=20x | | 2m+1-m=4 | | 3d-5=-1 | | d-8=9 | | (2a-3)(2a+3)=0 | | 4x^2-16x+25=0 | | 5x-6y=-8 | | 2y-2+14=21 | | X^2+5XY+6Y^2+X+2Y=2 | | 4x^2=-4x+3 | | 6x^3+15x^2-8x-20=0 | | 8x^5-10x^4+1=0 | | 3x+2=190 | | (9x^2)+(30x)=48 |